Interventionism in the Family: Does Adoption Law in England and Wales Advocate the ‘Theft’ of Children? - Richardson, Barbara Alice (Kent Law Review, 2016)
This article questions the use of interventionism by the State in child protection. The law of adoption is used to contrast the public’s apparent demand for the reduction of state control with children’s need and right of protection from neglect and maltreatment. Particular reference is made to the recent controversial rickets cases, as well as the Pacchieri case of 2013. This article points to academic, legal and public perspectives in order to include all competing arguments involved. Finally, the article aims to demonstrate that it is sometimes necessary to undermine the sanctity of the private sphere in order to protect the society’s most vulnerable - children.